Recurrent retroperitoneal Schwannomas displaying different differentiation from primary tumor: Case report and literature review - Li, Zhong-qi (BioMed Central, 2010)
BACKGROUND: Retroperitoneal Schwannomas are uncommonly found in the retroperitoneum and few of them show malignant transformation and invasion. Local recurrence are common in malignant Schwannomas with very few reports of tumor distinct differentiation at recurrences. CASE PRESENTATION: We report here a rare case of retroperitoneal schwannoma with multiple origins from retroperitoneum and pelvic wall. Pathological examination confirmed the case as a schwannoma with malignant transformation. Radical dissection of the tumors along with the sacrifice of adjacent sigmoid colon and left kidney failed to provide a cure for this patient. Due to tumor recurrence, a second and a third surgery of radical excision were performed 6 months and 17 months later after the first surgery, respectively. Histopathologic analysis identified that the recurrent tumors were different from the original schwannoma because of their smooth muscle-like differentiation. CONCLUSION: Malignant schwannomas are uncommon sarcomas with a high incidence of local recurrence. Distinct immunohistochemical staining results of the tumors at recurrence indicate their potential of smooth-muscle like differentiation. Radical excision of the tumors may provide benefit for their local recurrences.